Bosnia and Herzegovina : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2008)
Data dissemination practices in Bosnia and Herzegovina meet many of the General Data Dissemination System recommendations for dissemination of macroeconomic statistics in terms of coverage, periodicity, and timeliness. Executive Directors suggest strengthening the mandate of the Bosnia and Herzegovina Agency for Statistics (BHAS) to coordinate a cohesive national statistical program, finalizing and publishing the constant price gross domestic product (GDP) estimates and the expenditure components of GDP. It is also recommended that data validation at all stages be improved and that the accuracy and reliability of the final results be enhanced.